Henry James’s Experience of New York City in The American Scene - Kovács, Ágnes Zsófia (FOCUS: Papers in English Literary and Cultural Studies, 2006)
Apart from his fictional production, Henry James published an array of nonfictional works beside his critical essays: travel writings, articles on current political issues, volumes of autobiography, and even a philosophical essay. Early on in his career, he wrote nonfiction sometimes to make ends meet and as part of an extended literary apprenticeship (Anesko vii), but beginning with the Prefaces, perhaps overburdened by the present and tempted to turn back to the past, his production was mainly constituted by these nonfiction efforts. The name of this phase, the “fourth phase,” refers to William James’s comment on Henry’s The Golden Bowl in 1905. William disliked the style of Bowl, Henry’s third manner and expressed a need for a fourth, possibly more straightforward style (Caramello 464). Henry’s fourth manner, however, is wide off the mark William set: it can be seen as a modification of the third in two major respects: real material is handled and the genres relied on demand the use of the first person Henry had previously tried to avoid (464). Currently, Ross Posnock and Beverly Haviland called this part of James’s work his second major phase (1907-14), one of autobiography, cultural criticism, and aesthetics (Posnock, “Breaking the Aura” 23-24, Haviland xv). The pieces that constitute the phase are first and foremost The American Scene about James’s travels in the US, two and a half volumes of autobiography, articles and lectures, the Prefaces to The New York Edition, two novels, one of them unfinished, and further tales.